Evidence-based coaching as a supplement to traditional lectures: impact on undergraduates' goal attainment and measures of mental well-being - Atad, Ofer I; Grant, Anthony M (International journal of mentoring and coaching in education, 2021)
PurposeThis study aimed to examine how the effects of traditional tertiary education (lecture format) on various outcomes – including goal attainment, psychopathology (stress, anxiety and depression), resilience, solution-focused thinking and self-insight – compare to effects of traditional education supplemented by health coaching, delivered through Zoom video-conferencing.Design/methodology/approachThe study, which involved mature-age Israeli undergraduate students enrolled in a health promotion course (n = 178), used a randomized controlled between-subjects (pre-post) design. Participants were each randomly assigned to a traditional-education condition (n = 90) or to a coaching condition (n = 88). All participants attended 13 weekly course lectures; those in the coaching condition also participated in weekly Zoom-based coaching sessions, with trained health coaches. Each participant completed online questionnaire measures at the beginning and at the end of the semester. Data were analyzed using repeated-measures ANOVA.FindingsCompared with participants in the traditional-education condition, those in the coaching condition showed, over the course of the semester, significant improvement in goal attainment, solution-focused thinking, self-insight, resilience and psychopathology. Participants in the traditional-education condition showed no change in these measures.Originality/valueThe authors’ findings suggest that health coaching, as a supplement to traditional lectures, can enhance undergraduates' goal attainment and multiple facets of their mental well-being. These findings may have significant practical implications for the vast numbers of students struggling to cope in higher education systems worldwide. The authors further suggest a range of alternative, coaching-inspired interventions that do not require development of a full coaching program.